Comparative Analysis of Thermal and Hydraulic Performance Of PHE and S&T Heat Exchanger During Pasteurization of Mango Juice Using Nano fluid. - Kesari, Pankaj; Dey, Debashis; Sikata Samantaray, Dr. (International Journal of Engineering and Technology, 2018)
Food industries including dairy units, fruits and beverages industries are frequently exposed to thermal processing inside heat- exchangers. Today, the vital demands for any food and beverages industries are fluids having high heat transfer characteristics, low pumping power, easy cleaning surfaces and hygienic operations. In foodstuff process industries these necessities are often met by different heat exchanger typically, plate- heat exchanger and the shell & tube heat -exchangerÂ are widely used. A comparative study of performance of plate-heat exchanger (PHE) and shell & tube heat -exchangerÂ (S&T HE) using Al2O3/distilled water nanofluid during the thermal processing of mango juice is done. The heat exchanging fluids employed here are nanofluid acting as hot fluid and mango juice as cold fluid. The experiment is carried out at constant cold fluid inlet temperature i.e. 20Â°C with varying inlet temperature of hot fluids (50, 55, 60 and 65Â°C) and varying volume flow rates (4, 5, 6 and 7LPM) for three nanoparticle concentrations (0.1, 0.2 and 0.3% by weight). Experimental results confirms that the Plate-heat exchanger (PHE) have high heat flux increment which is twice that of shell & tube heat -exchangerÂ (S&T HE) with lower pressure drop. The S&T HE have higher pressure drop compared to the PHE i.e. 36 times at low flow rate and 40 times at higher volume flow rate The enhancement of Nu number in PHE is 39% than that of S&T HE.